BYL719, a new α‐specific PI3K inhibitor: Single administration and in combination with conventional chemotherapy for the treatment of osteosarcoma. Issue 4 (30th June 2014) - Gobin, Bérengère; Huin, Marc Baud'; Lamoureux, François; Ory, Benjamin; Charrier, Céline; Lanel, Rachel; Battaglia, Séverine; Redini, Françoise; Lezot, Frédéric; Blanchard, Frédéric; Heymann, Dominique
<x xml:space="preserve">Abstract</x> It has been established that disturbances in intracellular signaling pathways play a considerable part in the oncologic process. Phosphatidylinositol‐3‐kinase (PI3K) has become of key interest in cancer therapy because of its high mutation frequency and/or gain in function of its catalytic subunits in cancer cells. We investigated the therapeutic value of BYL719, a new specific PI3Kα inhibitor that blocks the ATP site, on osteosarcoma and bone cells. The in vitro effects of BYL719 on proliferation, apoptosis, and cell cycle were assessed in human and murine osteosarcoma cell. Its impact on bone cells was determined using human mesenchymal stem cells (hMSC) and human CD14+ osteoclast precursors. Two different murine preclinical models of osteosarcoma were used to analyze the in vivo biological activities of BYL719. BYL719 decreased cell proliferation by blocking cell cycle in G0/G1 phase with no outstanding effects on apoptosis cell death in HOS and MOS‐J tumor cells. BYL719 inhibited cell migration and can thus be considered as a cytostatic drug for osteosarcoma. In murine preclinical models of osteosarcoma, BYL719 significantly decreased tumor progression and tumor ectopic bone formation as shown by a decrease of Ki67+ cells and tumor vascularization. To explore the maximum therapeutic potential of BYL719, the drug was studied in combination with conventional chemotherapeutic drugs, revealing promising efficacy with ifosfamide. BYL719 also exhibited dual activities on osteoblast and osteoclast differentiation. Overall, the present work shows that BYL719 is a promising drug in either a single or multidrug approach to curing bone sarcoma.